A Comparison of Telephone and Texting Interventions for Persons with Schizophrenia Spectrum Disorders. (1st May 2014) - Beebe, Lora; Smith, Kathlene D.; Phillips, Chad
<x xml:space="preserve">Abstract</x> Problem-solving interventions are not routinely offered to persons with schizophrenia spectrum disorders (SSDs). Telephone calls and text messages are potential avenues to offer problem solving support. This study compared the effect of telephone calls only, text messages only, and both telephone calls and text messages on individuals' symptoms and medication adherence. Thirty outpatient participants with SSDs were randomly assigned to weekly telephone calls, daily text messages, or both for three months. Participants received monthly in-home pill counts and symptom assessments. Repeated measures ANOVA was significant (F (4, 26) = 4.2, p = 0.005) for symptom scores. Further work with larger, more diverse, samples is needed.